Longitudinal changes in depressive symptoms associated with social isolation after the Great East Japan Earthquake in Iwate Prefecture: findings from the TMM CommCohort study - Yuka Kotozaki; Kozo Tanno; Kotaro Otsuka; Ryohei Sasaki; Makoto Sasaki (BMC, 2023)
Abstract Background Whether past disaster experiences affect the association between changes in social isolation and depressive symptoms is largely unknown. This study examined the association between changes in social isolation and depressive symptoms among survivors who experienced earthquake damage in the aftermath of the Great East Japan Earthquake (GEJE). Methods We analyzed longitudinal data from 10,314 participants who responded to self-report questionnaires on the Lubben Social Network Scale-6 (LSNS-6) and the Center for Epidemiological Studies-Depressive Scale (CES-D) in both the baseline survey (FY2013 to FY2015) and follow-up survey (FY2017 to FY2019) after the GEJE. According to changes in the presence of social isolation (< 12 of LSNS-6) at two time points, participants were categorized into four groups: "not socially isolated," "improved socially isolated," "newly socially isolated," and "continuously socially isolated." At the follow-up survey, a CES-D score of ≥ 16 indicates the presence of depressive symptoms. The adjusted odds ratios (AORs) and 95% confidence intervals (CIs) were estimated using the logistic regression analysis to examine the influence of the change in social isolation over four years on depressive symptoms. Results Participants who were newly socially isolated had a significantly higher prevalence of depressive symptoms than those who were not socially isolated (AOR = 1.89, 95% CI = 1.61 − 2.23). In addition, AORs were highest for those who were continuously socially isolated and had experienced house damage (AOR = 2.17, 95% CI = 1.73 − 2.72) and those who were newly socially isolated and had not experienced the death of family members due to the GEJE (AOR = 1.88, 95%CI = 1.60 − 2.22). Conclusion Our longitudinal findings suggest that being newly or continuously socially isolated is associated with a risk of depressive symptoms, not only among those who had experienced house damage or the death of a family member, but also those who had not, in the disaster-affected area. Our study underlines the clinical importance of social isolation after a large-scale natural disaster and draws attention to the need for appropriate prevention measures.